2009
DOI: 10.1108/03090590910939049
|View full text |Cite
|
Sign up to set email alerts
|

Which factors affect entrepreneurial intention of university students?

Abstract: Purpose-Fostering entrepreneurship needs a twofold policy that should focus on both the current situation and future prospect of entrepreneurship. Although many scholars and policy makers devote their attention to the first foci of issue, it is equally important to map out the future context of entrepreneurship. The purpose of this paper is to fill this void by analysing the impacts of some contextual factors on entrepreneurial intention of university students. Design/methodology/approach-In the study, a model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
576
4
32

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 685 publications
(711 citation statements)
references
References 36 publications
(49 reference statements)
42
576
4
32
Order By: Relevance
“…SN is the main factor that indicates the students' intentions to be entrepreneurs. These results are not in agreement with the conclusions drawn by Turker & Selcuk (2009), according which social support does not have a great impact on entrepreneurial intentions and behavior. A possible explanation of these divergent results is that in Italy there is a lot of social pressure exercised by the people that students consider to be important in their lives, perhaps more so that many other countries.…”
Section: H5contrasting
confidence: 56%
See 1 more Smart Citation
“…SN is the main factor that indicates the students' intentions to be entrepreneurs. These results are not in agreement with the conclusions drawn by Turker & Selcuk (2009), according which social support does not have a great impact on entrepreneurial intentions and behavior. A possible explanation of these divergent results is that in Italy there is a lot of social pressure exercised by the people that students consider to be important in their lives, perhaps more so that many other countries.…”
Section: H5contrasting
confidence: 56%
“…Entrepreneurship researchers largely ignore the concept of self-efficacy despite its importance in predicting specific behaviors (Strecher et al, 1986;Harackiewicz et al, 2002). Self-efficacy has been associated with opportunity recognition and risk-taking (Krueger & Dickson, 1994;Krueger et al, 2000;Di Paola et al, 2016) as well as career choice (Bandura, 1986;Harackiewicz et al, 2002;Turker & Selcuk, 2009). On the basis of further literature, we can state the following hypothesis:…”
Section: Figure 1 Ajzen's Theory Of Planned Behavior (1985)mentioning
confidence: 99%
“…Pero al igual que en los anteriores, investigadores y en este caso educadores, no están de acuerdo en que un conjunto particular de cualidades sean la justificación para que una persona sea más emprendedora que otra, más bien, parece que hay un consenso en creer que es el estilo de enseñanza la clave de ese espíritu emprendedor. Demuestran que la iniciativa emprendedora está asociada a cualidades como la iniciativa, la creatividad y la autonomía (Lee, Chang & Lim, 2005;Türker, Onvural, Kursunluoglu & Pinar, 2005, Veciana, Aponte & Urbano, 2005Türker & Senem, 2008).…”
Section: Intención Espíritu Actitud Competencia E Iniciativa Persounclassified
“…The results showed that these named items are more important factors in the university. The results of Turker (2008) showed the supporting factors in the university affect the students' motivation for entrepreneurship. If the university develops such programs, the interest and motivation of students will increase.…”
mentioning
confidence: 97%